2020
DOI: 10.1111/gec3.12495
|View full text |Cite
|
Sign up to set email alerts
|

Land remediation, event spaces and the pursuit of Olympic legacy

Abstract: This paper explores the links between remediating land for Olympic event spaces and the pursuit of legacy. In particular, it considers ways in which redevelopment of the sizeable spaces prepared for staging the event take their place in broader strategies intended to bring long-term benefits to the host city and society in order to compensate for the costs and inconvenience originally incurred in hosting the Games. There are six main sections. The first analyses the diverse nature of brownfield land and highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In recent decades, mega-events 'seem to hold the potential and the capacity to achieve the necessary transformation' in host cities-especially those with declining economies or deteriorating urban spaces (Roult & Lefebvre, 2013). Gold and Gold (2020) further consolidated the links between remediating land for Olympic event spaces and pursuing a legacy. Chen (2015) examined how host cities have explored the Summer Olympic Games for urban transformation.…”
Section: Mega-events and Legacy Creation Before The Pandemicmentioning
confidence: 95%
“…In recent decades, mega-events 'seem to hold the potential and the capacity to achieve the necessary transformation' in host cities-especially those with declining economies or deteriorating urban spaces (Roult & Lefebvre, 2013). Gold and Gold (2020) further consolidated the links between remediating land for Olympic event spaces and pursuing a legacy. Chen (2015) examined how host cities have explored the Summer Olympic Games for urban transformation.…”
Section: Mega-events and Legacy Creation Before The Pandemicmentioning
confidence: 95%
“…Findings indicated that although Rio promised sustainable development in the area, there was a significant disconnect between the environmental sustainability promises and achievements. Similarly, Gold and Gold (2020) investigated the links between remediating land for the construction of Olympic venues and pursuing a legacy. They concluded that more comprehensive strategies are needed if the goal is to achieve long-term benefits to the host city and community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More specifically, the plan for the IOC (as the governing body of the Olympics) regarding sustainability is to ensure that both the Olympic and Paralympic Games are the leader in sustainability initiatives (Müller et al, 2021). In 2021, the Tokyo 2020 Olympic Games were held after a year of postponement due to the coronavirus pandemic (Triantafyllidis, 2020). Consequently, Tokyo 2020 Olympic Games brought the world together in times of two crises: the coronavirus pandemic, which caused the delay and nearly the cancelation of the Games, and climate change, which forced athletes and spectators to suffer in 40°C heat (Müller et al, 2021; Triantafyllidis, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation